2016
DOI: 10.1021/acs.inorgchem.6b01514
|View full text |Cite
|
Sign up to set email alerts
|

Ligand “Brackets” for Ga–Ga Bond

Abstract: The reactivity of digallane (dpp-Bian)Ga-Ga(dpp-Bian) (1) (dpp-Bian = 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene) toward acenaphthenequinone (AcQ), sulfur dioxide, and azobenzene was investigated. The reaction of 1 with AcQ in 1:1 molar ratio proceeds via two-electron reduction of AcQ to give (dpp-Bian)Ga(μ2-AcQ)Ga(dpp-Bian) (2), in which diolate [AcQ](2-) acts as "bracket" for the Ga-Ga bond. The interaction of 1 with AcQ in 1:2 molar ratio proceeds with an oxidation of the both dpp-Bian ligands as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 54 publications
8
34
1
Order By: Relevance
“…This was accompanied by the loss of carbon monoxide and the concomitant formation of two NÀCb onds. The GaN 3 C 2 (8): Ga(1)ÀGa(2) 2.4145(11), Ga(1)ÀN(2) 2.031(4),G a(1)ÀN(3) 1.886(4), Ga(1)ÀN(4) 1.906(4), Ga(2)ÀN(5) 1.872(4), Ga(2)ÀN(6) 1.875(4), O(1)À C(37) 1.214 (6), O(2)ÀC(41) 1.220 (5), N(2)ÀC(2) 1.288 (6), N(5)ÀC(45) 1.370 (6), N(6)ÀC(46) 1.368 (6),N(4)ÀC(41) 1.344 (6), N(4)ÀC(42) 1.489 (6), N(1)ÀC(1) 1.516 (6), N(1)ÀC(37) 1.418 (6),N (3)ÀC(37) 1.350 (6),N(3)ÀC(38) 1.474 (6),C (41)À C(1) 1.563 (7), C(45)ÀC(46) 1.378(6), C(1)ÀC(2) 1.556 (7), C(38)ÀC(39) 1.500 (8), C(39)ÀC(40) 1.301 (8);N (2)-Ga(1)-Ga(2) 126.87(12), N(4)-Ga(1)-Ga(2) 118.61 (14), N(2)-Ga(1)-Ga(3) 111.79(13), N(2)-Ga(1)-N(3) 93.32 (18), N(3)-Ga(1)-N(4) 109.08 (17), N(2)-Ga(1)-N(4) 93.40 (17) (6), Ga(1)ÀN(2) 1.943 (6), Ga(1)ÀC(59) 2.029(9), Ga(1)ÀN(6) 1.922 (7), Ga(2)ÀN(3) 1.922 (6), Ga(2)ÀN(4) 1.919 (6), Ga(2)ÀC(62) 2.019(9), Ga(2)ÀN(5) 1.948 (7), C(1)ÀN(1) 1.404(10), C(2)ÀN(2) 1.417(10), C(1)À C(2) 1.365 (11) ) 2 À NPh) with the same MN 3 C 2 ring as that in 7.D FT calculations revealed that the initial steps of the mechanism resemble the chain-growth process in the anionic polymerization of isocyanates and feature charge-separated intermediates. These steps are followed by ring-closure at the metal centero ft he last intermediate formedt oy ield as even-memberedm etallacycle, which then undergoes ar etro-CO insertiono ft he carbonyl group bonded to the metal center.…”
Section: Resultsmentioning
confidence: 99%
“…This was accompanied by the loss of carbon monoxide and the concomitant formation of two NÀCb onds. The GaN 3 C 2 (8): Ga(1)ÀGa(2) 2.4145(11), Ga(1)ÀN(2) 2.031(4),G a(1)ÀN(3) 1.886(4), Ga(1)ÀN(4) 1.906(4), Ga(2)ÀN(5) 1.872(4), Ga(2)ÀN(6) 1.875(4), O(1)À C(37) 1.214 (6), O(2)ÀC(41) 1.220 (5), N(2)ÀC(2) 1.288 (6), N(5)ÀC(45) 1.370 (6), N(6)ÀC(46) 1.368 (6),N(4)ÀC(41) 1.344 (6), N(4)ÀC(42) 1.489 (6), N(1)ÀC(1) 1.516 (6), N(1)ÀC(37) 1.418 (6),N (3)ÀC(37) 1.350 (6),N(3)ÀC(38) 1.474 (6),C (41)À C(1) 1.563 (7), C(45)ÀC(46) 1.378(6), C(1)ÀC(2) 1.556 (7), C(38)ÀC(39) 1.500 (8), C(39)ÀC(40) 1.301 (8);N (2)-Ga(1)-Ga(2) 126.87(12), N(4)-Ga(1)-Ga(2) 118.61 (14), N(2)-Ga(1)-Ga(3) 111.79(13), N(2)-Ga(1)-N(3) 93.32 (18), N(3)-Ga(1)-N(4) 109.08 (17), N(2)-Ga(1)-N(4) 93.40 (17) (6), Ga(1)ÀN(2) 1.943 (6), Ga(1)ÀC(59) 2.029(9), Ga(1)ÀN(6) 1.922 (7), Ga(2)ÀN(3) 1.922 (6), Ga(2)ÀN(4) 1.919 (6), Ga(2)ÀC(62) 2.019(9), Ga(2)ÀN(5) 1.948 (7), C(1)ÀN(1) 1.404(10), C(2)ÀN(2) 1.417(10), C(1)À C(2) 1.365 (11) ) 2 À NPh) with the same MN 3 C 2 ring as that in 7.D FT calculations revealed that the initial steps of the mechanism resemble the chain-growth process in the anionic polymerization of isocyanates and feature charge-separated intermediates. These steps are followed by ring-closure at the metal centero ft he last intermediate formedt oy ield as even-memberedm etallacycle, which then undergoes ar etro-CO insertiono ft he carbonyl group bonded to the metal center.…”
Section: Resultsmentioning
confidence: 99%
“…[7d, 21] The reactivity of GaÀGa-bonded compounds towards isothiocyanates has not been reported so far,a lthought he cleavage of SÀS, BiÀC, SbÀN, BiÀBi, and TeÀC single bonds andN ÀNd ouble bonds( 99.9 kcal mol À1 )w ith Ga compounds is known. [17,18,22] We demonstrate that digallanes 1 and 2 are able to cleave the very stable C=Sb ond (137 kcal mol À1 )o fi sothiocyanates. The C=Sb ond can also undergo [2+ +4] cycloaddition reactions to the GaN 2 C 2 ring to yield metallacycles.…”
Section: Introductionmentioning
confidence: 97%
“…α‐Diimine ligands proved to be successful in stabilizing a variety of low‐valent metal complexes, including group 13 metal–metal‐bonded compounds such as digallanes and dialumanes . These complexes have shown promising reactivity towards various small molecules, such as alkynes, alkenes, disulfides, azobenzenes, phenazine, sulfur dioxide, and ketone derivatives . Further, the α‐diimines are redox‐active ligands that can be easily oxidized or reduced, can serve as electron reservoirs, and allow significant extension of the reactivity of metal complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, compound 2 reacts with different alkynes to form cycloadducts that liberate “coordinated” alkyne upon heating . When combined with oxidizing reagents, compound 2 revealed an electron transfer dualism: depending on the substrate, oxidation may occur first on the ligands or involve the metal–metal bond . The substrates for oxidative addition reactions to complex 2 were limited to iodine and disulfides.…”
Section: Introductionmentioning
confidence: 99%